Photogrammetry and Remote Sensing for the identification and characterization of trees in urban areas. (May 2019) - Mueed Choudhury, Md Abdul; Costanzini, Sofia; Despini, Francesca; Rossi, Paolo; Galli, Andrea; Marcheggiani, Ernesto; Teggi, Sergio
Abstract: For the last few decades, there have been a lot of studies recognising the significant roles of the urban trees as a high-quality carbon sink. This work is a preliminary study about how remote sensing and photogrammetry could be useful tools to identify urban trees for the purpose of Carbon Storage (CS) computation in urban areas. Our first study area is a typical urban park located in Sassuolo, a municipality in the northern part of Italy in the so-called "Pianura Padana". We measured the tree Height (H) and the Diameter at Breast Height (DBH), required for the calibration of the CS, based on the tree allometry during the field data collection along with the constructing a 3D model through the photogrammetric approach. A high-resolution WorldView (WV) 3 satellite image of the same area, was classified using an object-oriented approach to count the number of trees varied with different species. This preliminary study will enhance the possibilities of the application of these approaches in case of the larger urban areas to ascertain the accuracy of the tree CS calibration.